The differentiate effects of resistance training with or without external load on young soccer players` performance and body composition - Falces-Prieto, M.; de Villarreal-Sáez, E. S.; Raya-González, J.; González-Fernández, F. T.; Clemente, F. M.; Badicu, G.; Murawska-Cialowicz, E. (Frontiers in Physiology, 2021)
Purpose: The purpose of this study was to examine the effects of 15 weeks (2/week) of two different resistance training (RT) programs [the self-load group (SG) vs. the overload group (OG)] on selected measures of physical performance in young male soccer players.